Pencabulan Anak Sebagai Penyimpangan Sosial: (Studi Kasus di Kota Tanjungpinang) - Laila Purnama Hilham; Rindhi Yani; Aulia Aulia; Dimas Agustio Alghifari; Muhammad Abror Atmaja (Pusat Riset dan Inovasi Nasional, 2026)
This journal examines the criminal act of child abuse as a form of social deviance in Tanjungpinang City, Riau Islands Province. The research uses a qualitative case study approach with data sources in the form of legal documents, media reports, and statistics on violence against children for the 2022–2025 period. The analysis is based on three sociological theories, namely Labeling Theory (Howard Becker), Social Control Theory (Travis Hirschi), and Anomie Theory (Robert Merton). The results of the study show that child abuse in Tanjungpinang is triggered by weakening family ties, exposure to pornographic content through technology, and socio-economic disparities. The impact experienced by victims is long-term, including physical and psychological trauma, feelings of betrayal, sexual trauma, helplessness, and social stigmatization. The study concluded that child abuse is not only a violation of the law, but also a complex social phenomenon. Therefore, a multi-stakeholder response is needed, including firm law enforcement, psychosocial support for victims, strengthening family roles, and increasing digital literacy to prevent exposure to risky content. These findings are expected to form the basis for more comprehensive and sustainable child protection policies at the local and national levels.